A Target Enablement Package for the Inhibition of SHIP1 as a Therapeutic Strategy for the Treatment of Alzheimer's Disease. (20th December 2022) - Richardson, Timothy I; Jesudason, Cynthia D; Lobb, Karen L; Durst, Gregory L; Clayton, Brent; Massey, Steven M; Beck, Daniel E; Zhang, Zhong‐Yin; Dong, Jiajun; Lin, Jianping; Miao, Jinmin; Putt, Karson S; et al.
Abstract: Background: Recent evidence including GWAS and differential gene expression comparing normal to affected Alzheimer's brain tissue have identified risk and protective variants in genes such as TREM2, PLCG2 and INPP5D that are essential to microglia function. INPP5D encodes SHIP1, a multi‐domain protein with a phosphatase that converts PI(3, 4, 5)P3 to PI(3, 4)P2, a SH2 domain that interacts with receptor ITAMs and competes with SYK, and a proline rich region that binds many other proteins. SHIP1 therefore limits microglia activation in multiple ways. Inhibition of SHIP1 early in disease would increase microglial protective functions and reduce the rate of disease progression and cognitive decline in Alzheimer's patients. Method: We performed a screen of 50K compounds at the SHIP1 phosphatase, analyzed a publicly available fragment‐based screen, and evaluated inhibitors reported in the literature. We utilized the malachite green assay with PtdIns(3, 4, 5)P3 ‐diC8 and SHIP1 Ptase‐C2 to measure inhibitory potency. A Cellular Thermal Shift Assay was used to confirm target engagement in cells. A high‐content imaging assay measuring phagocytosis, cell number, and nuclear intensity was implemented using the BV2 and HMC3 cell lines to characterize cellular pharmacology and cytotoxicity. Mouse microglia were assayed to demonstrate similar activity in primary cells. Inhibitors predicted to have drug‐like properties were subjected to assays measuring solubility, cellular permeability, and mouse microsomal stability. A physiological based pharmacokinetic model was compared to measured exposure in vivo for select compounds upon oral administration in mice. Result: SHIP1 inhibitors have been compared head‐to‐head in a set of assays relevant to both enzyme inhibition and microglia activation. Structurally distinct, novel, and selective SHIP1 inhibitors have been discovered. The enzyme mode of action, cellular activity and drug‐like properties were determined. Pharmacokinetic profiles were determined for inhibitors with sufficient cellular potency and drug‐like properties for in vivo studies in mice. Conclusion: Inhibition of SHIP1 is a novel therapeutic strategy for treatment of Alzheimer's. We identified structurally distinct molecular scaffolds with varying degrees of enzyme inhibition, cellular activity, and exposure in mice. Recommendations for use of probe molecules in target validation studies and the development of lead‐like molecules for clinical studies will be made.